Networks of PhD students and academic performance - Capó, Aina Maria (Metodološki zvezki, 2007)
In this article we compare regression models obtained to predict PhD students' academic performance in the universities of Girona (Spain) and Slovenia. Explanatory variables are characteristics of PhD student's research group understood as an egocentered social network, background and attitudinal characteristics of the PhD students and some characteristics of the supervisors. Academic performance was measured by the weighted number of publications. Two web questionnaires were designed, one for PhD students and one for their supervisors and other research group members. Most of the variables were easily comparable across universities due to the careful translation procedure and pre-tests. When direct comparison was not possible we created comparable indicators. We used a regression model in which the country was introduced as a dummy coded variable including all possible interaction effects. The optimal transformations of the main and interaction variables are discussed. Some differences between Slovenian and Girona universities emerge. Some variables like supervisor's performance and motivation for autonomy prior to starting the PhD have the same positive effect on the PhD student's performance in both countries. On the other hand, variables like too close supervision by the supervisor and having children have a negative influence in both countries. However, we find differences between countries when we observe the motivation for research prior to starting the PhD which increases performance in Slovenia but not in Girona. As regards network variables, frequency of supervisor advice increases performance in Slovenia and decreases it in Girona. The negative effect in Girona could be explained by the fact that additional contacts of the PhD student with his/her supervisor might indicate a higher workload in addition to or instead of a better advice about the dissertation. The number of external student's advice relationships and social support mean contact intensity are not significant in Girona, but they have a negative effect in Slovenia. We might explain the negative effect of external advice relationships in Slovenia by saying that a lot of external advice may actually result from a lack of the more relevant internal advice.
Keywords: Students; Študentje; Podiplomski študij; Postgraduate studies; Učinkovitost; Effectiveness; efficiency; Social networks; Družbena omrežja; Comparative analysis; Primerjalna analiza; Regresijska analiza; Regression analysis; Slovenia; Slovenija; Spain; Španija; analiza omrežij; družboslovno raziskovanje